A Systematic Review of the Provision of Sexuality Education to Student Teachers in Initial Teacher Education - Costello, Aisling; Maunsell, Catherine; Cullen, Claire; Bourke, Ashling (Frontiers in Education, 2022)
Teachers, and their professional learning and development, have been identified as playing an integral role in enabling children and young people’s right to comprehensive sexuality education (CSE). The provision of sexuality education (SE) during initial teacher education (ITE) is upheld internationally, as playing a crucial role in relation to the implementation and quality of school-based SE. This systematic review reports on empirical studies published in English from 1990 to 2019. In accordance with the PRISMA guidelines, five databases were searched: ERIC, Education Research Complete, PsycINFO, Web of Science and MEDLINE. From a possible 1,153 titles and abstracts identified, 15 papers were selected for review. Findings are reported in relation to the WHO Regional Office for Europe and BZgA (2017)Training Matters: Framework of core competencies for sexuality educators. Results revealed that research on SE during ITE is limited and minimal research has focused on student teachers’ attitudes on SE. Findings indicate that SE provision received is varied and not reflective of comprehensive SE. Recommendations highlight the need for robust research to inform quality teacher professional development practices to support teachers to develop the knowledge, attitudes and skills necessary to teach comprehensive SE.